2022
DOI: 10.1101/2022.02.01.22270122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with iron deficiency and how they can be used in blood donor selection processes

Abstract: Background and objectives: In an effort to improve donor health, we set out to investigate determi-nants other than blood donation that increase risk of ID in a healthy population and if they should be implemented into current blood donor selection processes. Methods: We systematically searched the PubMed, Ovid Medline and Scopus for articles related to ID. Results: Current evidence suggests that several determinants, including biological, environmental, lifestyle and socioeconomic factors increase the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, strong relationships between dietary iron load, its bioavailability, iron requirements, and iron stores [ 91 ] need to be mentioned. Dietary factors associated with iron deficiency were also suggested for implementation into blood donor selection processes [ 92 ]. On our Nutrihealth study sample we also found significant positive correlation of iron status biomarkers (haemoglobin and ferritin) with meat and fish, and with iron intake from meat and fish, but not with total iron intake ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, strong relationships between dietary iron load, its bioavailability, iron requirements, and iron stores [ 91 ] need to be mentioned. Dietary factors associated with iron deficiency were also suggested for implementation into blood donor selection processes [ 92 ]. On our Nutrihealth study sample we also found significant positive correlation of iron status biomarkers (haemoglobin and ferritin) with meat and fish, and with iron intake from meat and fish, but not with total iron intake ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%